Slow food: creación de un recetario para fomentar el turismo gastronómico en la ciudad de Otavalo-Ecuador - Balladares Sosa, Diego Javier (2024)
This research explores the potential of Otavalo, Ecuador’s local gastronomy to drive gastronomic tourism, focusing on the Slow Food movement as a way to preserve the region’s cultural and culinary identity. The main objective was to strengthen gastronomic tourism in Otavalo, Ecuador, through the creation of a recipe book that highlights the diversity and authenticity of its traditional cuisine, aligned with Slow Food values. The methodology included a literature review on Slow Food, an analysis of fresh, seasonal ingredients characteristic of the region, and surveys directed at residents and visitors to understand their perceptions and willingness toward local gastronomy and the use of a digital recipe book. Additionally, four interviews were conducted with three chefs and a tourism manager. The most relevant results include a list of fresh, seasonal products and a digital recipe book based on Slow Food principles. Twelve recipes are included, reflecting the tastes and preferences of survey respondents. The recipe book includes a QR code for easier distribution. It is concluded that the recipe book, as a gastronomic resource, could be essential in attracting visitors and educating locals on the value of consuming fresh, local, and sustainable products. This addresses the research question.